Does service sector growth cause agricultural and industrial development? A dynamic econometric approach - Stanley Emife Nwani; Ikechukwu Kelikume; Emeka Osuji (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
This article investigated the service sector linkages with agriculture and industrial sectors with the purpose of ascertaining if forward and backward causal-chain exists, and the direction of causation among these sectors. The study was prompted by obvious evidence that sectoral contributions to growth have defiled the tenets of theories in emerging markets. The study employed a dynamic econometric technique for causaleffect determination in the vector autoregressive (VAR) Granger causality test using annualized time series data on growth rate in service, industry and agriculture sectors between 1982 and 2018. The empirical results revealed a weak sectoral linkage between the service sector and other sectors of the economy. Specifically, service sector growth does not stimulate growth in other sectors but growth in agricultural and industrial sectors drives the service sector performance. This implies that service led growth is illusionary, thus, causes de-industrialization and inhibits agricultural development. On the premises of the empirical findings, the study recommends the need to intensify efforts that would stimulate and establish a synergy between the agricultural and industrial sectors. This will naturally spur growth in the service sector.
Keywords: C01; L60; L80; O40; 330; Service sector; industrial sector; agricultural sector; causality; vector autoregression and econometric approach